Future Problems in Logistics Due to Demographic Change - Matthias Klumpp; Sascha Bioly; Christian Witte (Next Generation Supply Chains: Trends and Opportunities. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
This research paper describes the impact of demographic change on the transport and logistics sector. Therefore, besides a literature review and a management option discussion in the end, the paper contains the following two main sections and methods: First an empirical report of a 2014 survey conducted in the research project "DO.WERT" regarding the working conditions of truck drivers in Germany (working hours, wages, motivation, qualification; n=483). Second, an optimization prognosis (GAMS conceptualization) for the German truck driver labor market in 2030 including increased traffic volumes, restricted carbon dioxide emissions as well as a market-based wage cost function draft. Existing research has shown that major disruptions in the "triangle" of increasing traffic volumes, decreasing populations and also politically intended decreases in carbon dioxide emissions have to be expected, for example for logistics wage and also freight rates markets.
10419/209187; https://econpapers.repec.org/RePEc:zbw:hiclpr:18
Keywords: 650; demographic change; transport volume simulation; road transport; wage simulation; transport mode prognosis